Keutamaan Beriman Kepada Kitab-Kitab Allah Dalam Membangun Ketakwaan dan Ketaatan - Mauizah Hanifah; Silvi Novtrianti; Zahrah Nabila; Firman Syaputra; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research is motivated by faith in the books of Allah which is one of the fundamental articles of faith in Islam. These holy books are not just historical records or documents of civilization, but are also divine guidance presented to guide humanity. The aim of this research is to create faith in Allah's books to strengthen piety and obedience to the Creator. The research method used is a qualitative research method that focuses on a descriptive-analytical approach. Qualitative research was chosen because the main aim of this article is to explore and understand the meaning of the primacy of believing in Allah's books in the context of building piety and obedience. The researcher concludes that the result of this article is that deep faith in His books is the main basis for living a life full of blessings. This faith not only brings a person to a high spiritual understanding, but also encourages him to implement God's teachings in real ways in everyday life, both in personal, social and spiritual aspects